Practitioner experiences of developing and implementing two UK ED-based hospital violence intervention programmes: a process evaluation - Moore, Simon; Van Godwin, Jordan; Moore, Graham; Hamilton, Megan; O'Reilly, David (Emergency medicine journal : EMJ, 2025)
EDs can address modifiable risks of patients attending due to violence. Hospital-based violence intervention programmes (HVIPs) can reduce patients' exposure to violence but can place additional burdens on staff. We explored practitioners' views on two nurse-led HVIPs' design and delivery, response to patient need, engagement with ED health professionals, adaptation to local context and analysed documents relevant to these objectives. This was a qualitative process evaluation, from January to September 2023, of two nurse-led HVIPs implemented in a major trauma centre and a large urban hospital in the UK. Interview participants (N=49) were involved with the commission and implementation of the HVIPs, or worked within the broader violence-prevention ecology. We gathered perspectives on intervention implementation and undertook documentary analysis on local and national policies, and guidance relating to HVIPs development, implementation and delivery (N=46). Documentary data were subject to thematic and content analyses, interview data to thematic analysis. HVIPs were developed in response to a perceived under-provision of services for patients attending EDs due to violence. The HVIP nurses had access to clinical records facilitating the identification of eligible patients. They provided patient-centred care, addressing needs through referrals into health and community-based services. Over 60% of eligible patients engaged. The nurses were seen as credible champions working towards a minimally burdensome service that supported and trained ED staff. Embedding HVIPs into usual care took time and was limited by the perceived short-term nature of the intervention. The implementation of nurse-led HVIPs enables access to clinical records, facilitating patient engagement, and can provide an additional service aligned to usual emergency care, supporting both patients and ED staff. The protocol was pre-registered (ISRCTN 15286575; March 13, 2023) and published before data collection was complete.